Energy and exergy analysis of coal-fueled fire tube alstom boiler using direct method: case study at garment factory - Trikusuma, Septian; Susastriawan, A.A.P.; Rusianto, Toto (Journal of Engineering and Applied Technology, 2025)
This research analyze the energy and exergy efficiency of coal-fueled fire tube Alstom boiler operating for five years (2019 – 2024) in garment factory using the direct method. Energy efficiency reflects how effectively coal energy is converted into steam, while exergy efficiency assesses the portion of that energy available for useful work. Results indicate a decline in energy efficiency from 75.92% in the first year to 65.47% in the fifth year due to scale buildup, increased heat loss through blowdown and flue gas, and component degradation. Similarly, exergy efficiency dropped from 24.45% to 22.00%, primarily due to heat loss from boiler walls and steam pipes, high-temperature flue gas, and combustion inefficiencies. A temporary efficiency increase in the fourth year resulted from improved maintenance, but the decline continued in the fifth year. These findings emphasize the need for regular maintenance and combustion optimization. Measures such as routine cleaning, fuel quality monitoring, and thermal insulation improvements can mitigate energy losses and enhance efficiency. Implementing these strategies can sustain or improve energy performance, contributing to industrial sustainability through more efficient energy consumption.